2021
DOI: 10.3390/plants10040698
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Rapid Micropropagation System for Kaempferia parviflora Wall. Ex Baker: Phytochemical Analysis of Leaf Extracts and Evaluation of Biological Activities

Abstract: This study aimed to establish a rapid in vitro plant regeneration method from rhizome buds of Kaempferia parviflora to obtain the valuable secondary metabolites with antioxidant and enzyme inhibition properties. The disinfection effect of silver oxide nanoparticles (AgO NPs) on rhizome and effects of plant growth regulators on shoot multiplication and subsequent rooting were investigated. Surface sterilization of rhizome buds with sodium hypochlorite was insufficient to control contamination. However, immersin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Leaves (3 months old) of KP-BG were collected from in-vitro-raised plantlets and exvitro (polyhouse)-grown plants. KP-BG plantlets were raised according to Park et al [23]. Briefly, surface-sterilized rhizome buds of KP-BG were cultivated on Murashige and Skoog (MS) basal medium with agar (0.8%), sucrose (3%), 6-benzyladenine (8.0 µM), and thidiazuron (0.5 µM) under 24 ± 1 • C and a 16 h photoperiod (40 µmol s −1 m −2 ) for shoot induction.…”
Section: Plant Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Leaves (3 months old) of KP-BG were collected from in-vitro-raised plantlets and exvitro (polyhouse)-grown plants. KP-BG plantlets were raised according to Park et al [23]. Briefly, surface-sterilized rhizome buds of KP-BG were cultivated on Murashige and Skoog (MS) basal medium with agar (0.8%), sucrose (3%), 6-benzyladenine (8.0 µM), and thidiazuron (0.5 µM) under 24 ± 1 • C and a 16 h photoperiod (40 µmol s −1 m −2 ) for shoot induction.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The total carotenoid, flavonoid, phenolic, essential oil, and alpha-tocopherol contents in leaves of several Kaempferia spp. have been reported [22,23,26,27]. Chan et al [22] reported that the total phenolic content and antioxidant capacity were higher in the leaf extract than in the rhizome extract of K. galanga.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations